Application of electrical resistivity tomography (ERT) in uranium mining earth dam - Moreira, Cesar Augusto [UNESP]; Guireli Netto, Leonides [UNESP]; Camarero, Pedro Lemos [UNESP]; Bertuluci, Fernanda Barbosa [UNESP]; Hartwig, Marcos Eduardo; Domingos, Reinaldo (Oxford University Press (OUP), 2022)
Dams are built to contain water or mining tailings and provide several benefits to society. The safety and stability of these structures are essential since eventual accidents can generate catastrophic damage. The main cause of ruptures is associated with abnormal seepage, which can progress to an internal erosion process. To assess the stability and safety of dams, periodic inspections are carried out, which typically include visual inspections and geotechnical instrumentation. Some geophysical methods have the potential to assist conventional geotechnical instrumentation using non-destructive and rapid acquisition investigations. The present study applied a finite element forward modeling to evaluate the percolation conditions and water stability in an earth dam of a decommissioned uranium mine in Brazil. The dam is the final structure of the contention system of mine water treatment. The electrical resistivity data were acquired using electrical resistivity tomography (ERT) and Schlumberger array. The results were presented from the inversion of data in 3D models. The data were processed by open-source software (modeling and inversion of geophysical data). The results indicate the presence of water in the vertical filter located in the crest area. The different levels of investigation indicated water infiltration in the rock mass of the dam foundation. These results are supported by structural surveys carried out in the area that indicate a fracturing pattern in the rock mass of the mine area. The results of the study were satisfactory for the desired purposes and demonstrate that geophysical methods constitute an important complementary tool for the geotechnical monitoring dams.
Keywords: dams; geophysics; mining; modeling; seepage